PENGEMBANGAN E-MODUL BERBASIS MOBILE LEARNING UNTUK MATA KULIAH METODE PENELITIAN - Nusrotus Saidah (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this research is to develop mobile learning-based e-module teaching materials for research methods courses.This research method is a research and development method using the ADDIE model with e-module development steps, namely: 1) Analysis; 2) Design; 3) Development; 4) Implementation; 5) Evaluation. The sample in this study were all tarbiyah students, namely the PAI study program who took research methods courses, namely semester 5 with a total of 93 students. The sampling technique is a saturated sample technique from the population used as a sample in the study. The data collection techniques of this research are observation, questionnaires and documents. This research instrument is in the form of expert validation sheets and practical assessments by students. This research design is experimental with pre-post test only design with piared sample t test analysis.The results showed that the analysis of product design and data that could be presented in expert judgment showed that the e-module had very good criteria with a significance value of 0.000 0.005, which means that there is a significant difference between learning before and after learning using e-modules based on mobile learning. E-module has a very practical assessment by students as a reference in independent learning with an average score of 4.5 with a very good category. This e-module provides an alternative for students to learn independently, more efficiently and effectively in the learning process outside the classroom.